MEDIATING COUNTER-RELIGIOUS INTOLERANCE IN CONTEMPORARY INDONESIA: A Critical View - Susilawati, Susilawati; Surur, Misbahus (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This article seeks to analyze the pros and cons regarding radicalism on YouTube. The focus of this article is on how the concept of counter-radicalism is expressed in the LogIn content on the Deddy Corbuzier and Ustaz Abdul Somad Officials YouTube Channel. On other hand, this article also examines how the effectiveness of the two channels in the context of deradicalizing religious understanding and countering intolerance. Methodologically, this article uses a Critical Discourse Analysis (CDA) approach based on Norman Fairclough’s three-dimensional theory: text, discourse practice, and socio-cultural. This article argues that the percentage of success in countering intolerance and radicalism in LogIn content (religious dialogue) is more than the content of Ustaz Abdul Somad Official. Deddy Corbuzier’s YouTube channel—which broadcasts the LogIn program—has more subscribers than Ustaz Abdul Somad Official. Furthermore, the concept of delivering dakwah (preach) in the LogIn program is also more varied, attractive, and contemporary. Thus, it is more interesting to netizens from various religious backgrounds, rather than the content of Ustaz Abdul Somad Official.